PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA PADA MATERI ASAS BERNOULLI KELAS XI SMA BERBASIS ANALISIS TES KEMAMPUAN RESPONDEN - Pebriyanti, Gita Wahyu; Imansyah, Harun; Wijaya, A. F. C.; Rusnayati, Heni (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Based on previous research through the questionnaire and test in one of the High School in Bandung, more than 50% of students experienced epistemological learning obstacles on the dynamic fluid material and 66,2% students couldnÃ¢â‚¬â„¢t answer the test about BernoulliÃ¢â‚¬â„¢s principle. The aim of this study is to identify the studentÃ¢â‚¬â„¢s epistemological learning obstacles profile of grade XI BernoulliÃ¢â‚¬â„¢s principle material, based on the respondentÃ¢â‚¬â„¢s ability test. Epistemological learning obstacles occur due to limitation of knowledge to a certain concept and it will lead to obstacles in using their knowledge when facing different concept. The method is qualitative descriptive, combined with the historical approach analysis through the respondentÃ¢â‚¬â„¢s ability test in the form of three essays covering essential concepts of BernoulliÃ¢â‚¬â„¢s principle, which given to the students in one of the High School in Bandung. The average score 68,27% is the students who experienced obstacles about BernoulliÃ¢â‚¬â„¢s equation in TorricelliÃ¢â‚¬â„¢s principle, 95,36% is the students facing obstacles about BernoulliÃ¢â‚¬â„¢s equation in VenturiÃ¢â‚¬â„¢s principle, and 87,05% the students obstacles on BernoulliÃ¢â‚¬â„¢s principle in aircraft lift force. The conclusion is the encounter of epistemological learning obstacles on BernoulliÃ¢â‚¬â„¢s principle material, there must be effort to minimize learning obstacles. Keywords: Learning obstacles, Bernoulli’s principle, Respondent’s Ability Test.